Economic Specialties Students’ Motivation Towards Developing Intercultural Competence - Zelikovs’ka, Olena (Pedagogical Discourse, 2012)
The article highlights the results of the research of the essence of the notions „motivation” and „needs”, different approaches to classification of the motives and mechanisms of influence on students’ cognitive activity. Factors which affect the development of positive motivation towards gaining intercultural competence have been identified.